THE NEED TO ENHANCE ONLINE CONSUMER PROTECTION UNDER EXISTING SAUDI ARABAIN E-COMMERCE LAWS - Aloufi, Abdulrahman (Curtin University, 2023)
This thesis identifies the shortcomings of the Kingdom of Saudi Arabia’s existing consumer protection laws in terms of e-commerce transactions, including the KSA's new draft consumer protection law. It also compares KSA legal frameworks to that of some Gulf Co-operation Council countries, namely the United Arab Emirates, Qatar and Kuwait, in order to find a solution to the identified gaps that KSA policymakers can adopt or adapt.